6. Administration of Centella Leaf Extract (Centella asiatica (L.) Urban) for Decreasing cAMP Responsive Element Modulator (CREM) Expression in Testicular Seminiferous Tubule of Male Rats (Rattus norvegicus) - Susi Darmayanti; Sri Wahyuni; Muslim Akmal; Tongku Nizwan Siregar; Sugito Sugito (The Faculty of Veterinary Medicine of Syiah Kuala University, 2016)
The objective of this study was to determine the effect of centella leaf extract administration on decreased of the molecule cAMP responsive element modulator (CREM) expression in the testicular seminiferous tubules of male rats (Rattus norvegicus). Eight rats, aged 3.5 months with 150-250 grams of body weight (BW) were used in this study. All rats were divided randomly into four groups as if K0 as a control group whereas K1, K2, and K3 were given the centella leaf extract with doses 125, 250, and 500 mg / kg body weight respectivelly that given once daily for 30 days. At the end of the treatment, rats were sacrificed and their testes were collected and subsequently fixed in buffered neutral formalin (BNF) 10% as fixative solution for histological preparation. The CREMs expressions were detected using immunohistochemical methods. The results showed that the number of CREM expression in the seminiferous tubules significantly differ (P 0.05) between K0 and the treatment group (K1, K2, and K3). Conclusion, the administration of centella leaf extract with of the dose 125, 250, and 500 mg/kg BW can decreased CREM expression spermatids of testicular seminiferous tubules in male rat.